Utilization of Digital Banking Services for Generation Z Economic Sustainability - Abdillah, Aris; Basuki, Hari; Santoso, Wibowo Iman; Sukresna, I Made; Indriani, Farida (LifeSciFi, 2024)
Digitalization in banking has changed the way banks operate and interact with their customers. Starting with the emergence of ATM machines, then developing into internet banking and mobile banking, and now comes with various e-wallet and fintech applications that offer convenience in transactions. Generation Z as digital native really benefits from this development because they can easily take advantage of the digital services provided by banks to support their transactions. Even so, not many Gen-Z realize the importance of utilizing banking products for their future (both for investment and protection) because they tend to have impulsive consumption behaviour. Many factors cause a lack of awareness of the need to do investment and to have protection, one of which is their low financial literacy. This article aims to identify and analyse the benefits of digital banking services in three main aspects: transactions, savings, investment, and protection. With a focus on generation Z in Indonesia, this article will discuss how these services can support future economic sustainability. This article was prepared using a literature study method by analysing previous scientific articles that discussed the topic of digital banking and its implications for economic growth and financial stability from the perception of Generation Z.